SELECTED MEASURES OF HUMAN AND SOCIAL CAPITAL OF POLISH MUNICIPALITIES AND THE QUALITY OF LIFE IN MUNICIPALITIES – CORRELATIONS AND MANAGERIAL IMPLICATIONS - Śmietanko, Tomasz (Management and Administration Journal, 2025)
Human and social capital is a key success factor in managing organizations, especially in the commercial sector. This is confirmed by the very large literature on the subject. The present study, however, proposes a different perception of a specific “organization” as a community of residents in a specific territory, empowered organizationally, legally and financially through the municipal government. In such a view, this success and at the same time the result of management should be the quality of life of residents and sustainable development. The purpose of this article is to examine the relationship between municipalities' non-finan-cial capitals and the quality of life in municipalities and to identify the management implications for municipal authorities that result from this relationship. The article carries out a study of selected literature on the subject. The subject of our own research is 30 Polish municipalities of urban-rural, district cities of land districts (10 of low wealth, 10 of medium wealth and 10 of high wealth. As a result of the research, the existence of a very strong correlation between selected measures of human capital and quality of life in municipalities and a strong correlation between selected elements of social capital and quality of life in municipalities was established. The analyses provided new information on the impact of the studied non-financial capitals on the quality of life in municipalities and the formulation of management implications and recommendations for municipalities on this basis.